Identifikasi Tahap Kesesuaian Pengelolaan Limbah Medis Di Rumah Sakit Z Kota Bandung - Oktavian, Rizky Taufiq; Pharmawati, Kancitra (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Hospitals are places that have a higher risk of health problems for both healthy and sick people. Medical waste produced by hospitals affects human health, therefore the purpose of this study was to determine the level of suitability of medical waste management at Hospital Z in Bandung City. Solid medical waste has various types, such as infectious, pathological, sharp, pharmaceutical, cytotoxic, chemical, radioactive, and waste with high heavy metal content. The purpose of this study was to evaluate the suitability of solid medical waste management at Hospital Z according to relevant regulations. Primary and secondary data were collected for this study and the data were processed using a Likert scale scoring. The study includes reduction, sorting, containerization, symbols and labels, collection, storage and transportation between the existing conditions and PerMenLHK No. 56/2015, PerMenLH No. 14/2013. The results of the identification of the suitability of medical waste management in Hospital Z obtained a score of 91%, which is included in the very good category.